Intracavernous delivery of clonal mesenchymal stem cells rescues erectile function in the streptozotocin‐induced diabetic mouse. (29th December 2015) - Ryu, J.‐K.; Kim, D.‐H.; Song, K.‐M.; Ryu, D.‐S.; Kim, S.‐N.; Shin, D.‐H.; Yi, T.; Suh, J.‐K.; Song, S. U.
Summary: The major hurdle for the clinical application of stem cell therapy is the heterogeneous nature of the isolated cells, which may cause different treatment outcomes. The aim of this study was to examine the effectiveness of mouse clonal bone marrow‐derived stem cells (BMSCs) obtained from a single colony by using subfractionation culturing method for erectile function in diabetic animals. Twelve‐week‐old C57BL/6J mice were divided into four groups: controls, diabetic mice, and diabetic mice treated with a single intracavernous injection of PBS (20 μL) or clonal BMSCs (3 × 10 5  cells/20 μL). Clonal BMSCs were isolated from 5‐week‐old C3H mice. Two weeks after treatment, erectile function was measured by electrical stimulation of the cavernous nerve. The penis was stained with antibodies to PECAM‐1, smooth muscle α‐actin, neuronal nitric oxide synthase (nNOS), neurofilament, and phosphorylated endothelial NOS (phospho‐eNOS). We also performed Western blot for phospho‐eNOS, and eNOS in the corpus cavernosum tissue. Local delivery of clonal BMSCs significantly restored cavernous endothelial and smooth muscle cell contents, and penile nNOS and neurofilament contents, and induced eNOS phosphorylation (Ser1177) in diabetic mice. Intracavernous injection of clonal BMSCs induced significant recovery of erectile function, which reached 80–90% of the control values. Clonal BMSCs successfully restored erectile function through dual angiogenic and neurotrophic effects in diabetic mice. The homogenous nature of clonal mesenchymal stem cells may allow their clinical applications and open a new avenue through which to treat diabetic erectile dysfunction.